Self-concept of EFL Pre-service Teachers: A Reflection from a Teacher Practicum in Indonesia Context - Dina Rachmawati; Emi Emilia; Iwa Lukmana (Journal of English Language Studies, 2017)
This study is intended to determine the self-concept of English Foreign Language (EFL) Pre-service Teachers. The self-concept used in this study was adapted from the self-concept of Burns, (1982) and the Teachersâ€™ Competence of Indonesia Government Regulation no. 19 article 28 (2005). The self-concept is divided into three aspects: academic self-concept, which is comprised of pedagogic and professional self-concept, social self-concept, and emotional self-concept. The data was collected through the five Likert-scale of closed-ended questionnaire. The questionnaire contains thirty items which represent the aspects of self-concept. The questionnaire was distributed to fifty participants of a pre-service program of English Education Department of Indonesia University of Education. Descriptive statistics were used to analyze the data. The findings show that most of the participants in this study have medium and high average on the three aspects of self-concept. The findings suggest that the participants of this study perceive themselves as prospective English teachers positively.Â Key words: Pre-service Teachers; Pre-service teaching program; Self-concept